Quien danza, ¿qué alcanza? - Wurzba, Lilian (Escritura e Imagen, 2008)
This article aims to reflect on dance’s signification as a gesture that can become a possibility of communion between the sacred and the profane. This communion is expressed in the human being’s experience incarnated as the inner search for completeness, for meeting with totality. The basis of argument is the Carl Gustav Jung’s psychology theory and the contributions of religion historian Mircea Eliade.